Optimization of Increasing Learning Motivation and Entrepreneurial Interest for Students at the Al-Imran Orphanage, Gowa Regency - Retyana Wahrini; Supriadi; Hasbi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The process of applying the knowledge learned at the University to help society as a whole is known as community service activities. At the Al Imran Orphanage in Gowa Regency, South Sulawesi, is a place for implementing community service activities that aim to encourage students' interest in entrepreneurship, especially to help the community around the orphanage. In this community service activity, children at the orphanage are taught how to make